2017
DOI: 10.1002/ajoc.201700209
|View full text |Cite
|
Sign up to set email alerts
|

Superior Alkylating Agents for Bulky Esters/Ketones via Strontium‐Mediated Barbier‐Type Reaction

Abstract: An efficient methodh as been developed for the Barbier-typea lkylation reaction of bulky esters or ketones in the presence of metallic strontium and alkyl iodides. The reactionp roceeded smoothly at ambient temperature to afford the fully alkylated corresponding alcohols in better yield than those obtained when using the corresponding Grignard reagents. The method is especially effective for introducing isobutyl or neopentyl groups into phenyl or adamantyls keletons.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Figure 2 displayed the few examples of butyrolactone based drugs. On the basis of their exciting profile in the pharmacological field, butyrolactone and its derivatives have been developed by various research group across the globe; however, most of these strategies are multi-step reactions and require additives (K2CO3, TFA, In(OTf)3, Yb(OTf)3, p-TSA , HCl, TfOH, NH4Cl, K2HPO4), expensive reagents and long reaction times followed by tedious work up and purification methods [29][30][31][32][33][34][35]. Among the developed approaches, Barbier-type allylation strategy remains the key approach towards in the fabrication of these bioactive molecular architectures [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 displayed the few examples of butyrolactone based drugs. On the basis of their exciting profile in the pharmacological field, butyrolactone and its derivatives have been developed by various research group across the globe; however, most of these strategies are multi-step reactions and require additives (K2CO3, TFA, In(OTf)3, Yb(OTf)3, p-TSA , HCl, TfOH, NH4Cl, K2HPO4), expensive reagents and long reaction times followed by tedious work up and purification methods [29][30][31][32][33][34][35]. Among the developed approaches, Barbier-type allylation strategy remains the key approach towards in the fabrication of these bioactive molecular architectures [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have reported the preparation and reactivity of organostrontium compounds. 7–10 Our group has already reported the smooth alkylation of aldehydes 11 or imines 12 and the dialkylation of an ester 13 using metallic Sr and alkyl iodide under mild conditions. 14 The electronegativity of Sr is close to that of Li and Mg (Li = 0.98, Mg = 1.31, Sr = 0.95 on the Pauling scale, respectively), 15 but Sr has a larger ionic radius (Li + = 76, Mg 2+ = 72, Sr 2+ =118 in pm, respectively).…”
mentioning
confidence: 99%